TRAC 2014 - Brindle, Tom; Brindle, Tom; Allen, Martyn; Allen, Martyn; Durham, Emma; Durham, Emma; Smith, Alex; Smith, Alex (Oxbow Books, 2015)
This volume contains a selection of papers presented at TRAC 2014, as well as some invited contributions. In keeping with the aims of TRAC, several papers make make innovative use of interdisciplinary theory: in humanistic geography, philosophy and archaeology; social psychology; and the cognitive science of religion in the study of Roman monuments, military social history and religion. Other papers share a common theme: the critical interpretation of archaeological evidence. A more careful consideration of non-grave good pottery sherds from graves suggests that these often disregarded items p